2010
DOI: 10.1590/s0100-69912010000200005
|View full text |Cite
|
Sign up to set email alerts
|

Repercussão da perda de peso sobre parâmetros nutricionais e metabólicos de pacientes obesos graves após um ano de gastroplastia em Y-de-Roux

Abstract: Repercussão da perda de peso sobre parâmetros nutricionais e metabólicos de pacientes obesos graves após um ano de gastroplastia em Y-de-Roux 97 Rev. Col. Bras. Cir. 2010; 37(2): 096-101 peso acarretaria não só redução de PCR como também de interleucina-1 concomitantemente à diminuição na resistência periférica à insulina, diminuindo o risco de doença cardiovascular 8 . . . . . Sabe-se que, embora ocorra melhora clíni-ca após tratamento cirúrgico, o paciente necessitará de acompanhamento nutricional regular co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1
16

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 25 publications
(28 reference statements)
1
10
1
16
Order By: Relevance
“…Observou-se que após a cirurgia ocorreu redução de peso e do IMC em todas as participantes e, na maioria dos casos, mudanças na classificação do IMC, resultados esperados após a aplicação dessa técnica cirúrgica que consiste na redução do tamanho do estômago, com redução da área absortiva. Dados da literatura descrevem que os primeiros seis meses após a cirurgia são os de perda de peso mais significativa, estabilizando-se após dois anos e podendo inclusive ocorrer recidiva do peso após certo tempo [19][20][21][22][23]. Essas informações são coerentes com os achados do presente estudo, que mostram uma perda ponderal maior nas mulheres com período de até…”
Section: Discussionunclassified
“…Observou-se que após a cirurgia ocorreu redução de peso e do IMC em todas as participantes e, na maioria dos casos, mudanças na classificação do IMC, resultados esperados após a aplicação dessa técnica cirúrgica que consiste na redução do tamanho do estômago, com redução da área absortiva. Dados da literatura descrevem que os primeiros seis meses após a cirurgia são os de perda de peso mais significativa, estabilizando-se após dois anos e podendo inclusive ocorrer recidiva do peso após certo tempo [19][20][21][22][23]. Essas informações são coerentes com os achados do presente estudo, que mostram uma perda ponderal maior nas mulheres com período de até…”
Section: Discussionunclassified
“…Surgical treatment is the most effective for patients with class III obesity 6 . This study observed an average weight loss of 35.05 ± 10.47 kg (26.98%) and a decrease in the BMI of 11.6 ± 4.99 kg / m² in the first six months after the operation.…”
Section: Overall Ratingmentioning
confidence: 99%
“…The vitamin A deficiency may be present in individuals with NAFLD, contributing to the disease, since these individuals are more susceptible to oxidative stress which, by itself, greatly increases the consumption of substances having antioxidant function 27 . Observing the results and efficiency of surgical treatment of class III obesity to reduce the complications of this disease 3,6 , including hepatic steatosis 23 , it was proposed to evaluate the relationship between nutritional status of vitamin A, by serum retinol and β-carotene, and the regression of hepatic steatosis in patients undergoing Rouxen-Y gastric bypass in (RYGB) for the treatment of class III obesity.…”
Section: Introductionmentioning
confidence: 99%
“…Characterized as a chronic disease with a multifactorial etiology, environmental factors and a genetic predisposition appear to be the main cofactors 1 . There are several factors that act and interact in the regulation of food intake and energy deposition, contributing to the development and maintenance of obesity, including: endocrinal, adipose, intestinal and neuronal factors 2 .…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is considered a risk factor for many diseases that contribute to increased morbidity and mortality, such as type 2 diabetes mellitus, dyslipidemia, hypertension, ischemic heart disease, strokes and some types of cancer 1 . The main modifiable risk factor in the development of coronary artery disease is obesity, giving it a degree of cardiovascular risk similar to that associated with hypertension, hyperlipidemia, smoking and sedentarism 4 .…”
Section: Introductionmentioning
confidence: 99%